It seems to me : selected letters of Eleanor Roosevelt. - Roosevelt, Eleanor, 1884-1962 (The University Press of Kentucky, 2015)
One of the most important women of the 20th Century, Eleanor Roosevelt (1884-1962) was also one of its most prolific letter writers. Yet never before has a selection of her letters to public figures, world leaders, and individuals outside her family been made available to general readers and to historians unable to visit the archives at Hyde Park. It Seems to Me demonstrates Roosevelt's significance as a stateswoman and professional politician, particularly after her husband's death in 1945. These letters reveal a dimension of her personality often lost in collections of letters to family mem.